2014
DOI: 10.1073/pnas.1315156111
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmaaldolase is required for metabolism but dispensable for host-cell invasion

Abstract: Gliding motility and host-cell invasion by apicomplexan parasites depend on cell-surface adhesins that are translocated via an actinmyosin motor beneath the membrane. The current model posits that fructose-1,6-bisphosphate aldolase (ALD) provides a critical link between the cytoplasmic tails of transmembrane adhesins and the actin-myosin motor. Here we tested this model using the Toxoplasma gondii apical membrane protein 1 (TgAMA1), which binds to aldolase in vitro. TgAMA1 cytoplasmic tail mutations that disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 30 publications
8
99
0
Order By: Relevance
“…An association between the cytoplasmic tail of AMA1 and aldolase 17,21,26 was previously reported, and proposed to act as a bridge with F-actin and the gliding machinery necessary for internalization. However, a recent report revisiting the implication of aldolase in gliding and invasion 27 showed that aldolase does not have an essential role in coupling AMA1 or other MIC proteins to the actomyosin system during invasion. How the AMA1 tail functions during internalization remains an important question for the future.…”
Section: Discussionmentioning
confidence: 99%
“…An association between the cytoplasmic tail of AMA1 and aldolase 17,21,26 was previously reported, and proposed to act as a bridge with F-actin and the gliding machinery necessary for internalization. However, a recent report revisiting the implication of aldolase in gliding and invasion 27 showed that aldolase does not have an essential role in coupling AMA1 or other MIC proteins to the actomyosin system during invasion. How the AMA1 tail functions during internalization remains an important question for the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TgALD-depleted T. gondii parasites showed a defect in motility and invasion, and a substantial loss of fitness 89 . However, another report showed that this fitness loss could be due to an accumulation of toxic metabolites caused by incomplete glycolysis, which cast some doubt on the role of TgALD as a connector 90 . Finally, TgALD was proven dispensable for gliding in parasites that are grown in the absence of glucose 90 .…”
Section: Secretory Organelles Deliver Adhesinsmentioning
confidence: 99%
“…However, another report showed that this fitness loss could be due to an accumulation of toxic metabolites caused by incomplete glycolysis, which cast some doubt on the role of TgALD as a connector 90 . Finally, TgALD was proven dispensable for gliding in parasites that are grown in the absence of glucose 90 . The physiologically relevant glideosome-associated connector (GAC) was discovered following the functional characterization of a large armadillo repeats-containing protein that accumulates at the apical tip of T. gondii tachyzoites and in the invasive stages of malaria parasites 40 .…”
Section: Secretory Organelles Deliver Adhesinsmentioning
confidence: 99%
“…MIC2 is the transmembrane (TM) member of the complex, with an extracellular region composed of an integrin-like I-domain followed by five thrombospondinlike repeats (TSRs) and a degenerate sixth TSR near the TM domain. The C-terminal cytosolic tail is thought to interact with the actin-myosin motility system, but the molecular basis of this connection remains to be determined (9,10).…”
mentioning
confidence: 99%